The Impact of Residual Retinal Fluid Following Intravitreal Anti-Vascular Endothelial Growth Factor Therapy for Diabetic Macular Edema and Macular Edema Secondary to Retinal Vein Occlusion A Systematic Review - Patil, Nikhil S (Ophthalmic surgery, lasers & imaging retina, 2023)
The association between residual retinal fluid and visual acuity for diabetic macular edema (DME) and macular edema (ME) secondary to retinal vein occlusion (RVO) is not well established. We conducted a systematic literature search for peer-reviewed articles reporting on visual acuity stratified by subretinal fluid (SRF), intraretinal fluid (IRF), or any retinal fluid at final follow-up after intravitreal anti-vascular endothelial growth factor therapy injection for treatment of DME or ME secondary to RVO. Two observational studies on ME secondary to RVO and one study for DME found no significant differences between eyes with and without residual retinal fluid for final BCVA. One randomized controlled trial (RCT) found that eyes with residual retinal fluid had significantly worse final best-corrected visual acuity in ME secondary to RVO, whereas another RCT found no significant difference for DME. There is a paucity of evidence examining the impact of residual retinal fluid on visual acuity in DME and ME secondary to RVO. The limited evidence suggests that aggressive fluid resolution is worthwhile. [Ophthalmic Surg Lasers Imaging Retina 2023;54:50-58.]